Ocular gun-shot injuries in Ibadan (1991)
Twenty patients with eye injuries resulting from gun-shots were admitted to the University College Hospital, Ibadan, over a 10-year period. Three of the patients had involvement of both eyes, making a total of 23 eyes. Seven eyes had contusion injuries, while 16 had perforating injuries. Eight of the perforating group had primary evisceration, two refused evisceration and six had repair of corneal! corneo-scleral wounds. All seven eyes in the contusion group were treated conservatively and four retained a vision of better than 6/36. Seven out of the 20 patients were shot by someone else, six of whom were armed robbers. The other 13 patients were shooting animals while hunting, when the gun either backfired or exploded in their faces.